The Evolving Role of Commercial Publishers and the Future of Open Access Repositories: The Potential of Corporate Social Responsibility - Koutras, Nikos (2019)
Since the modes of publishing content have changed in the digital age, Open Access (OA) practice could be an effective response towards the challenges generated by the ongoing technological advancements. It could respond to the competing concerns of copyright protection and equitable access to information, simultaneously. The paper analyzes the interconnections between commercial publishers’ and authors’ interest and argue that Open Access Repositories could be considered as an instrument towards common benefits. In the context of continuous technological growth OA could be also seen as an alternative instrument for the protection of intellectual property to facilitate modern or digital publishing and benefit publisher and intellectual creator, as well. Traditionally, commercial publishers are ‘gatekeepers’ of the standards of merit of academic works even though they get almost all of the profits. However, while they rely on academics’ expertise to remain commercially viable they do not pay for this expertise, appropriately. In contemporary days it is feasible for authors to not rely on commercial publishers. It is therefore in the interests of commercial publishers that academics keep publishing with them. As gatekeepers of standards of merit they can benefit the academic world and remain viable themselves. This claim will be substantiated with examples of relevant licensing forms and other initiatives of OA.